Ion-transfer electrochemistry of rat amylin at the water–organogel microinterface array and its selective detection in a protein mixture - De Eulate, Eva; O'Sullivan, Shane; Fletcher, Sharon; Newsholme, Philip; Arrigan, Damien (© 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim, 2013)
The behaviour of proteins and polypeptides at electrified aqueous-organic interfaces is of benefit in label-free detection strategies. In this work, rat amylin (or islet amyloid polypeptide) was studied at the interface formed between liquid aqueous and gelled organic phases. Amylin is a polypeptide that is co-secreted with insulin from islet beta-cells and is implicated in fibril formation. In this study, rat amylin was used, which does not undergo aggregation. The polypeptide was found to undergo an interfacial transfer process, from water to the gelled organic phase under applied potential stimulation. The voltammetry exhibited steady-state forward and peak-shaped reverse voltammograms, which are consistent with a diffusion-controlled water-to-organic transfer and a thin-film stripping or desorptive back-transfer. The diffusion-controlled forward current was greater when amylin was present in an acidic aqueous phase than when it was present in aqueous phase at physiological pH, reflecting the greater charge on the polypeptide under acidic conditions. The amylin transfer current was concentration-dependent over the range 2 - 10 µM, at both acidic and physiological pH. At physiological pH, amylin was selectively detected in the presence of a protein mixture, illustrating the bioanalytical possibilities for this electrochemical behaviour.